The role of teaching institutions to prepare and promote social entrepreneurs - Santos, Paula Marques dos (2020)
This research intends to analyse how Universities must have an important role in social entrepreneurship promotion and in the regional and social sustainable development itself. In fact, it's our opinion that students must be advised how can they start up their professional careers in social area and how they can be competitive in the professional world. Thus, academic curricula and teaching methodologies must give them the basic tools so they can have entrepreneurial spirit and to develop innovative programmes/organizations as well as, at the same time, to contribute for a more inclusive society.